Modeling of Acoustic Coupling of Ultrasonic Probes for High-Speed Rail Track Inspection - Sławomir MACKIEWICZ; Zbigniew RANACHOWSKI; Tomasz KATZ; Tomasz DĘBOWSKI; Grzegorz STARZYŃSKI; Przemysław RANACHOWSKI (Archives of Acoustics)
The paper presents the modeling of transmission of the ultrasonic plane wave through an uniform liquid layer. The considered sources of the ultrasonic wave were normal (straight) beam longitudinal wave probes and angle beam sheer waves probes commonly used in non-destructive testing. Coupling losses (CL) introduced by the presence of the coupling layer are discussed and determined applying the numerical procedure. The modeling applies to both monochromatic waves and short ultrasonic pulses with a specified frequency bandwidth. Model implementation and validation was performed using a specialized software. The predictions of the model were confirmed by coupling losses measurements for a normal beam longitudinal wave probe with a delay line made of polymethyl methacrylate (PMMA). The developed model can be useful in designing ultrasonic probes for high-speed rail track inspections, especially for establishing the optimal thickness of the water coupling layer and estimation of coupling losses, due to inevitable changes of the water gap during mobile rail inspection.